APPLICATION OF RATION FORMULATION BASED ON AGRICULTURAL WASTE AS GOAT COMPLETE FEEDING IN KALIMPORO VILLAGE, JENEPONTO REGENCY - Fika Yuliza Purba; Muhammad Ardiansyah Nurdin; Nur Alif Bahmid; Muhammad Ihsan Andi Dagong; Renny Fatmyah Utamy; Irwan Ismail; Soedarmanto Indarjulianto; Subaedy Yusuf (Universitas Airlangga, 2023)
This community service was carried out in Kalimporo Village, Jeneponto Regency, South Sulawesi, and aimed to increase farmers' knowledge, especially the Kalimporo Village farmers group, regarding the utilization and processing of agricultural waste into complete feed for livestock. Community Service was held on Sunday, 4th June 2023 in Kalimporo Village, Jeneponto Regency, South Sulawesi, attended by 25 out of 30 farmers (83.3%). The method used was discourse and plot demonstration. The results of this community service were the use of several types of agricultural waste such as bran, green bean skin, corn cobs, lamtoro, cassava, copra meal, and pollard available around the village to be formulated into complete feed with added minerals and salt. The ration was tested in the laboratory and showed good quality with a crude protein content of 12.13%. The feed was highly palatable when given to the goats. Ration based on agricultural waste can be used as a complete feed for goats with economic value so as to reduce livestock production costs and improve the farmers' well-being in Kalimporo Village, Jeneponto Regency, South Sulawesi.